The Effect Of Participative Leadership Style And Supportive Organizational Culture On Job Satisfaction Among Generation Z Employees In Indonesia With Work-Life Balance As An Intervening Variable - Afif Fadil; Suhartini (Cita konsultindo, 2026)
The increasing presence of Generation Z in the Indonesian workforce has driven organizations to reassess leadership approaches and organizational practices to meet evolving employee expectations. This study aims to examine the effect of participative leadership style and supportive organizational culture on job satisfaction among Generation Z employees in Indonesia, with work-life balance serving as an intervening variable. A quantitative explanatory research design was employed, and data were collected through a structured questionnaire distributed to Generation Z employees across various industries using purposive sampling. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that participative leadership and supportive organizational culture have significant positive effects on job satisfaction. Both variables also significantly influence work-life balance, which, in turn, has the strongest positive effect on job satisfaction. Furthermore, work-life balance was found to partially mediate the relationship between participative leadership and job satisfaction as well as between supportive organizational culture and job satisfaction. These findings highlight the importance of inclusive leadership practices and supportive organizational environments in fostering work-life balance and enhancing job satisfaction among Generation Z employees. This study contributes to the human resource management literature by empirically validating the mediating role of work-life balance and provides practical insights for organizations seeking to improve job satisfaction and retention of Generation Z employees.